'Be Angry But Do Not Sin' (Ephesians 4:26a): Sin and the Emotions in the New Testament with Special Reference to Anger. (February 2015) - Barton, Stephen C.
A presupposition of this essay is that a Christian understanding of sin should give attention to the emotions (or passions). Taking anger as a case in point, an account is offered of the paraenēsis in Eph. 4:26 where anger and sin are juxtaposed. The main argument is that the teaching about anger has to be situated in relation to the moral-theological vision of Ephesians as a whole, central to which is the coming together as one of Jews and Gentiles in the Church. Anger is a sin, if it undermines the eschatological oneness of the Body of Christ.